Community Development to Empower Intellectually Disabled Community Beyond The Program "Karangpatihan Bangkit" - Rosilawati, Yeni; Amalia , Dinar Ayu (Technium Social Sciences Journal, 2021)
People with intellectual disabilities in Indonesia are a group that needs targeted support in their lives. Everyone has the right to a decent life which is adaptive to his or her health and well-being. Karangpatihan is a village called Kampung Idiot (Idiot Village) because 86 of its people suffer from various levels of intellectual disabilities. A community development program in the form of a self-help group (SHG) named Rumah Harapan Karangpatihan Bangkit aimed to improve the social and economic capabilities of people with intellectual disabilities in Karangpatihan Village, Ponorogo, Indonesia. The researcher applied a qualitative method of research in the form of a case study. Data collection techniques used in this study were in the form of an in-depth interview with the Head of the Karangpatihan Village, managers of the Rumah Harapan Karangpatihan Bangkit as well as the people with intellectual disabilities involved in the program. Secondary data were obtained through the official SHG Rumah Harapan Karangpatihan Bangkit reports and mass media news clippings. The results showed that: (1) the community development program was successfully implemented by mentoring people with intellectual disabilities through various training activities such as crafts, catfish cultivation, animal husbandry as well as batik making; (2) the success of the program was supported by the active role of facilitators and the participation of local communities. The program was able to improve the lives and skill repertoire of the intellectually disabled. Therefore, they are able to be independent and creative while having a job and an income.